Postoperative clinical outcome and complications of combined cannulated cancellous screw with Kirschner wire in adolescent femoral neck fractures - Kenmegne, Guy Romeo; Zou, Chang; Lin, Yixiang; Yin, Yijie; Huang, Shengbo; Fang, Yue (Frontiers in Pediatrics, 2023)
Purpose Fractures of the femoral neck account for less than 1% of pediatric and adolescent fractures. Due to the high incidence of complications, and the age of the patients, the choice of fixation approach remains controversial among orthopedic surgeons. This study aimed to evaluate the postoperative outcomes and complications of femoral neck fracture in adolescents with open physis, following transphyseal fixation using a combined cannulated cancellous screw and Kirschner wire fixation. Methods Data of 19 patients aged between 12 and 19 years from January 2010 to January 2021 were retrospectively studied. The follow-up period was 1–11 years (5.83 ± 3.76 years). The variables of interest including demographic and clinical variables [age, BMI, gender, side of injury, fracture classification, operation time, time to surgery, and length of hospital stay (LOS)], postoperative outcomes, and complications (fracture healing time, nonunion, coxa vara, osteoarthritis, avascular necrosis, screw loosening, and femoral shortening) were analyzed. The assessment of the hip function was done on the final follow-up using the Ratliff scoring system. Results There was a male predominance of 76%; the mean age was 16.14 ± 1.57 years and the most frequent mechanism of injury was fall from a height. Delbet type II and III were the most encountered. The mean intraoperative time was 54.71 ± 7.85 min, the LOS was 8.34 ± 1.81days, and the time to surgery was 2.60 ± 1.16 days; the fracture healing time was 3.31 ± 1.04 months. The postoperative complications encountered were coxa vara osteoarthritis, spontaneous dislocation, and neck shortening. Clinical assessment revealed good results in 89% of patients and fair results in 11% of patients. Conclusion Transphyseal fixation using cannulated cancellous screw combined with Kirschner wire in our patients provided acceptable results. Thus, this approach can be a viable alternative in the management of adolescent femoral neck fracture with open physis.